Students’ Affective Silence in English Classroom Interaction - Muhayyang, Maemuna; Nasta, Mardiyanah; G, Hasriani; Sakkir, Geminastiti (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. This study is to describe the influencing factors of students’ affective silence in English classroom interaction. It used descriptive qualitative method taking all twelfth-grade students of science class consisting of 31 participants as the data resources. Three instruments were utilized to gain the data, namely (1) observation, (2) questionnaire, and (3) interview. The findings of this study show that there were ten affective factors influencing students’ silence in the classroom. They are (1) feeling nervous, (2) lack of self-esteem, (3) lack of self-confidence, (4) fear of making mistakes and worrying about other people's judgment, (5) worrying about their inability, (6) feeling unable to meet the teacher's expectations, (7) students’ personality, (8) avoiding awkwardness, (9) feeling embarrassed, and (10) avoiding showing off their ability. These factors empirically indicate that students' silence during the teaching and learning process takes place in the classroom is not always influenced by their cognitive inability but the affective aspect turns out to be something that quite dominates their inability to express themselves. Based on these findings, it takes into account that the students were not able to participate in teaching and learning process because of affective factors that trigger their inactivity.Keywords: Affective, Passiveness, Silence